PERAN PENGUSAHA PENGURUSAN JASA KEPABEANAN (PPJK) DALAM PROSEDUR KEGIATAN IMPOR DAN PENERAPAN PAJAK DALAM RANGKA IMPOR PADA PT. VALVE MANDIRI INDONESIA SURABAYA - Anindya Kiara Aisyiya Situsmara; Sri Luayyi; Eni Srihastuti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Import activities have a vital role in maintaining the economic stability of a country because they directly affect the amount of foreign exchange. Import activities are also closely related to the customs process in the recipient country, which supports cooperation between countries in international trade and influences the expansion of the market for goods and services in a country. In carrying out import activities, there are procedures that must be followed to comply with applicable regulations and to prevent possible losses for importers and exporters. The purpose of this research is to find out the role of Customs Management Services Entrepreneurs (PPJK) in import activity procedures and the application of taxes in the context of imports. This research was conducted at PT. Valve Mandiri Indonesia using primary data. The data analysis technique used is qualitative data analysis. Based on the results of the analysis, it was found that the role of Customs Service Entrepreneurs in import activities for importers has a complementary relationship. Middle to upper scale importers who import regularly may not use the services of Customs Management Services Entrepreneurs because they already have their own Export-Import division.